SUATU DESKRIPSI TENTANG PENERIMAAN PAJAK DALAM NEGERI INDONESIA PERIODE 1990 – 2007 - Parmadi, Parmadi (Jurnal Paradigma Ekonomika, 2011)
Development income tax revenue, value added tax and excise tax in nominal terms continues to increase, where as the real experience fluctuations, it is because the instability of the Indonesian economy. The contribution of real income tax receipts, real value added tax, and excise tax on real government revenue has increased every year during the period 1990 - 2007 the average of each for 46.47 percent, 33.27 percent and 8.57 percent. Comparison acceptance of the Gross Domestic Product (tax ratio) continues to increase, during the period 1990 to 2007 the average tax ratio for Indonesia was 10.53 percent. In the year 2007 tax ratio reached 13.01 percent of Indonesia. Keywords : income tax, value added tax,  excise tax, tax structure, tax ratio